Public accountability and transparency : the imperatives of good governance - Godbole, madhav (New Delhi : Orient Longman, 2003)
This book looks at the concepts of public accountability and transparency$1 (Bthe two critical prerequisites of good governance. Covering a wide range of institutions$1 (Bgovernmental and non-governmental$1 (Bthe precepts of public accountability and transparency are examined in the wider context of parliamentary institutions and their procedures and practice, electoral reforms, the executive wing of the government, the corporate sector, the cooperative sector, the judiciary, the media and civil society.s
Includes index.
Keywords: Public administration -- Moral and ethical aspects -- India; Political ethics -- India